The early history of radio from Faraday to Marconi - Garratt, G. R. M. (Gerald Reginald Mansel) 1906-1989 (Institution of Electrical Engineers, in association with the Science Museum, 1994)
Much has been written about Faraday and Marconi and about the history of the development of radio from the time of Marconi. However, Gerald Ganatt's special interest was in what might be termed the 'pre-history of radio'. The book therefore outline the sequence of development from Faraday's first prediction and concept of the electromagnetic field. Maxwell worked out the mathematics of electromagnetic wave propagation and here demonstrated their physical existence. Lodge identified the need of resonance between transmitter and receiver, thus leading Marconi's successful practical application.